Critical temperatures and pressures, heat capacities, and thermal diffusivities of γ-valerolactone and some alkyl pentanoates. (October 2020) - Nikitin, Eugene D.; Popov, Alexander P.; Bogatishcheva, Nataliya S.; Faizullin, Mars Z.
Highlights: Critical properties, heat capacities, and thermal diffusivities were measured. Measurements were performed for liquid γ-valerolactone and four n-alkyl pentanoates. The thermal conductivities of the compounds under study were calculated. γ-Valerolactone is an intermediate in the process of biomass conversion into fuels. Alkyl pentanoates are motor fuels produced from biomass. Abstract: The critical temperatures, pressures, heat capacities, and thermal diffusivities of γ-valerolactone and methyl, ethyl, butyl, and pentyl pentanoates have been measured. Heat capacities and thermal diffusivities have been measured at atmospheric pressure in the temperature ranges from 298.15 K to 473.15 K and from 303.15 K to 383.15 K, respectively. Experimental critical constants have been compared with those calculated using the group contribution methods of Wilson and Jasperson, Jobak, Constantinou and Gani, Marrero and Gani, and Hukkerikar et al. The thermal conductivities of the compounds under study have been calculated using experimental data. The temperature dependencies of heat capacities, thermal diffusivities, and thermal conductivities have been approximated by third-order and first-order polynomials. The coefficients of these polynomials have been given. Experimental heat capacities have been compared with those estimated by the methods of Kolska et al.